2014
DOI: 10.1111/1541-4337.12059
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Relationships between Processing, Food Structure, and Rheological Properties of Plant‐Tissue‐Based Food Suspensions

Abstract: Nowadays, there is much interest in controlling the functional properties of processed fruit-and vegetablederived products, which has stimulated renewed research interest in process-structure-function relations. In this review, we focus on rheology as a functional property because of its importance during the entire production chain up to the moment of consumption and digestion. This review covers the literature of the past decade with respect to processstructure-rheology relations in plant-tissue-based food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 173 publications
(326 reference statements)
2
45
0
Order By: Relevance
“…This result is in line with that of Woolfe et al () on okra mucilage. Other authors have observed similar effects of particle concentration on other plant‐tissue‐based suspensions (Moelants et al, ). Increasing the water content above a certain level reduces hydrodynamic interactions between particles, which modifies the flow properties of purées (Moelants et al, ).…”
Section: Resultssupporting
confidence: 62%
“…This result is in line with that of Woolfe et al () on okra mucilage. Other authors have observed similar effects of particle concentration on other plant‐tissue‐based suspensions (Moelants et al, ). Increasing the water content above a certain level reduces hydrodynamic interactions between particles, which modifies the flow properties of purées (Moelants et al, ).…”
Section: Resultssupporting
confidence: 62%
“…Particle size plays an important role on rheology and functionality of BGC because different particles fractions have different constituents and particle size distribution (PSD) impart the rheology differently. The effect of the particle size and PSD on the rheological characteristics of plant‐tissue‐based foods is not unambiguous (Moelants and others ). Limited research has been carried out on the functionality and rheological behavior of BGC and the contribution of individual particle size into rheology and viscoelasticity are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of activities seems to agree with the trend for starch yield obtained due to the enzyme treatment (Table 3). Hence, the responses observed are largely due to the different amounts and/or type of fiber materials (including pectic substances) present (Moelants et al, 2014). Apparently, pectic substances from especially, the Nkabom and the Esam bankye varieties were low in their polygalacturonan (PG) contents which probably explain why these varieties required relatively lower dosages (0.02%) and shorter holding times for maximum activity.…”
Section: Effects Of Enzyme Dosage On Starch Yield and Reaction Timementioning
confidence: 99%